2022
DOI: 10.1101/2022.03.18.22272595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating diagnostic noise in panel-based genomic analysis

Abstract: Background: Gene panels with a series of strict variant filtering rules are often used for clinical analysis of exomes and genomes. Panels vary in size, which affects the sensitivity and specificity of the test. We sought to investigate the background rate of candidate diagnostic variants in a population setting using gene panels developed to diagnose a range of heterogeneous monogenic diseases. Methods: We used the Genotype-2-Phenotype database with the Variant Effect Predictor plugin to identify rare non-syn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Indeed, large numbers of variants that have historically been considered to be pathogenic (associated with specific health outcomes) have in fact turned out to be common in individuals who do not show the associated phenotype (36), suggesting that either their original classification was wrong, or that their impact on health is more subtle or contextdependent than previously appreciated. Beaumont et al (37) illustrated the challenge of interpreting people's genomic data, showing that while large gene panels may maximize diagnostic yield, they are also likely to identify several variants that look hypothetically concerning though are probably benign: most people have at least one rare variant in the coding regions of the genome in panels containing over five hundred disease genes. Even for 'well-understood' pathogenic genetic variants, context matters: Jackson et al (38) found that people with cancer-predisposing genetic variants were at significantly less elevated risk of cancer in the absence of a family history.…”
Section: The Meaning Of a Genetic "Result"mentioning
confidence: 99%
“…Indeed, large numbers of variants that have historically been considered to be pathogenic (associated with specific health outcomes) have in fact turned out to be common in individuals who do not show the associated phenotype (36), suggesting that either their original classification was wrong, or that their impact on health is more subtle or contextdependent than previously appreciated. Beaumont et al (37) illustrated the challenge of interpreting people's genomic data, showing that while large gene panels may maximize diagnostic yield, they are also likely to identify several variants that look hypothetically concerning though are probably benign: most people have at least one rare variant in the coding regions of the genome in panels containing over five hundred disease genes. Even for 'well-understood' pathogenic genetic variants, context matters: Jackson et al (38) found that people with cancer-predisposing genetic variants were at significantly less elevated risk of cancer in the absence of a family history.…”
Section: The Meaning Of a Genetic "Result"mentioning
confidence: 99%
“…Clinical WES data interpretation relies on filtering and prioritization for rare genetic variants in disease-gene panels, which are subsequently interpreted in the context of the patient's clinical presentation [5]. Whereas this strategy is essential to identify the disease-causing variant(s), it is estimated that, depending on the number of genes included in the panel, dozens of variants are prioritized as diagnostic noise [6] -and this number is expected to rise even more in the coming years with technological innovations such as genome sequencing finding their way into the diagnostic arena [7][8][9].…”
Section: Introductionmentioning
confidence: 99%